Sociological analysis of appeal of small business in modern conditions - Kubrakova E. I. (Interactive science, 2017)
current economic situation doubts all universal approaches to investment attractiveness rating of small business in large cities of the Russian Federation. This problem starts to appear in small cities too. According to the authors, there appears necessity in determining citizen attitude to entrepreneurs and business generally.
Keywords: малый бизнес; государственная поддержка; small business; бизнесмен; кризисные условия; образ бизнесмена; businessman; crisis conditions; governmental support; businessman image